Through Wall Gap Detection Using Monostatic Radar - Elboushi, A.; Sebak, A. R.; Denidni, T. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a new experimental system for through wall gap detection and concealed vacancies behind wall is introduced. The ultra wide band (UWB) system is based on the principles of time domain reflectometry (TDR) and ground-penetrating radar (GPR) for through wall imaging to detect hidden gaps and/or hiding persons behind walls. The system uses a very short pulse generated by the vector network analyzer (VNA) to illuminate the wall under investigation through an UWB antenna probe. The detection process is achieved using time domain measurements of the probe reflection coefficient S11. Some numerical analyses have been carried out for verifying the principle of operation. The experimental results show a great ability not only for the gap detection between walls but also for estimation of the gap width with a very good accuracy (6.25 % in the worst case) for different types of walls.